2017
DOI: 10.1007/s11126-017-9534-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Preliminary Effectiveness of a Peer-Delivered and Technology Supported Self-Management Intervention for Older Adults with Serious Mental Illness

Abstract: To assess the feasibility, acceptability, and preliminary effectiveness of a peer-delivered and technology supported integrated medical and psychiatric self-management intervention for older adults with serious mental illness. Ten older adults with serious mental illness (i.e., schizophrenia, schizoaffective disorder, bipolar disorder, or major depressive disorder) and medical comorbidity (i.e., cardiovascular disease, obesity, diabetes, chronic obstructive pulmonary disease, hypertension, and/or high choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 33 publications
2
105
0
1
Order By: Relevance
“…Promising evidence indicates that a smartphone-based intervention appears to be an increasingly useful device for fidelity-adherent peer-delivered care. For example, a pilot study, N =8, found that certified peer specialists are providing evidence-based integrated self-management training with the assistive use of guided eModules (i.e., guided web-based curriculum) augmented by a smartphone application (PeerTECH) [15]. Emerging data from pilot studies and the findings in this report indicate support for further research on the effectiveness and implementation of peer evidence-based illness self-management interventions.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Promising evidence indicates that a smartphone-based intervention appears to be an increasingly useful device for fidelity-adherent peer-delivered care. For example, a pilot study, N =8, found that certified peer specialists are providing evidence-based integrated self-management training with the assistive use of guided eModules (i.e., guided web-based curriculum) augmented by a smartphone application (PeerTECH) [15]. Emerging data from pilot studies and the findings in this report indicate support for further research on the effectiveness and implementation of peer evidence-based illness self-management interventions.…”
Section: Discussionmentioning
confidence: 75%
“…A pilot study found that the combination of peers and mobile health (mHealth) was feasible and acceptable [15]. This pilot led to improvements in psychiatric self-management, self-efficacy for managing chronic health conditions, hope, quality of life, medical self-management skills, and empowerment [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bene cial effects of technology use on self-management and health outcomes were typically reported in studies that addressed non-professional social support by the patient's personal networks (37,38). The use of social media, online communities, or mobile health (mHealth) has enhanced or improved psychological empowerment (39,40), self-care information and knowledge (38,41), blood glucose levels (HbA1c), as well as glucose self-monitoring and physical activity (3,42), and other health topics (43)(44)(45). The inclusion of family members or spouses in technological diabetes management systems was found to improve their understanding of self-management requirements and affected the communication about diabetes and the support of the patient positively (46).…”
Section: Social Support and Technology-supported Diabetes Self-managementioning
confidence: 99%